Urgensi Judicial Review dalam Tata Hukum Indonesia - Huda, Ni’matul (Jurnal Hukum IUS QUIA IUSTUM, 2009)
The attendence of institution which has an authority to conduct judicial review in the perspective of democratic state will establish a system to mantain the democratic mechanism to be done  in the framework of democratic legal state.